2012
DOI: 10.1111/fme.12008
|View full text |Cite
|
Sign up to set email alerts
|

Resilient recreational fisheries or prone to collapse? A decade of research on the science and management of recreational fisheries

Abstract: Are recreational fisheries resilient to harvest or prone to collapse? This paper reviews research published since that question was posed by Post et al. (2002, Fisheries 27, 6–17). A number of patterns and processes have been identified that suggest understanding the risk of collapse requires knowledge of the fishing effort response, degree of depensation in the fishery and the life history of the harvested species. Processes involving the behaviour of fish, behaviour of anglers and management responses to dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
135
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(138 citation statements)
references
References 70 publications
2
135
1
Order By: Relevance
“…For example, a coarser survey design would have provided angling effort and a CPUE for the entire complex and we would have missed that relationship between angling effort and CPUE at the individual lake, which has implications on how angling effort could be managed in this system of lakes (Martin and Pope, 2010) and increase the resiliency of the fishery (Post, 2013). Furthermore, the creel survey used in this study revealed that anglers rarely move among lakes during a single trip; that is when an angler decides to fish at a given lake they stay at that lake during the fishing trip.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a coarser survey design would have provided angling effort and a CPUE for the entire complex and we would have missed that relationship between angling effort and CPUE at the individual lake, which has implications on how angling effort could be managed in this system of lakes (Martin and Pope, 2010) and increase the resiliency of the fishery (Post, 2013). Furthermore, the creel survey used in this study revealed that anglers rarely move among lakes during a single trip; that is when an angler decides to fish at a given lake they stay at that lake during the fishing trip.…”
Section: Discussionmentioning
confidence: 99%
“…Reservoir drawdowns can also aff ect anglers, including loss of boat ramp availability, loss of amenities for bank anglers, and changes in catch or harvest rates (Heman et al 1969;Post 2013). During periods of low water, anglers can choose to take up a diff erent recreational activity (e.g., golf), choose to continue fi shing at the reservoir and maintain their behavior, choose to continue fi shing at the reservoir but alter their fi shing behavior, or choose to fi sh a substitute reservoir within a regional fi shery (Martin and Pope 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recreational harvest is an integral component of most inland fisheries in North America, Europe, and Australia that affects population viability, community interactions, and fishery quality (Isermann and Paukert, 2010;Post, 2013). As such, regulating the harvest of fish by anglers is a common practice within fishery management.…”
Section: Introductionmentioning
confidence: 99%